Analisis Permodalan Koperasi Simpan Pinjam dalam Meningkatkan Kesejahteraan Anggota - Ramdana Irsyad, Ferozi; Rolas Olivia Naibaho, Angelina; Edi Saputra, Zaki; Alawiyah Matondang, Khairani (SJEE (Scientific Journals of Economic Education), 2025)
Savings and Loan Cooperatives (SLCs) play a strategic role in supporting the community’s economy, particularly by providing capital access to small and medium enterprises and enhancing the welfare of their members. However, the gap between capital needs and availability remains a major challenge for many SLCs. This study aims to analyze the capital structure and strategies of cooperatives in relation to improving member welfare, using a case study of KSP Nusa Indah. The research uses a qualitative descriptive approach through a literature study method, collecting data from literature sources, financial reports, and institutional documents. The results show that cooperative capital—whether sourced from internal funds or external loans plays a vital role in providing both productive and consumptive loans to members. Internal capital is considered more sustainable because it is interest-free and supports the increase of the cooperative’s net income (Sisa Hasil Usaha/SHU), which has a direct impact on member welfare. The success of cooperatives in enhancing welfare is also influenced by active member participation, financial literacy, and the integration of technology in data management and service delivery. Therefore, strengthening capital structures and cooperative governance is key to creating a sustainable economic impact for members.